Content and context boosting for mobile landmark recognition - Yap, Kim-Hui (2013)
Existing mobile landmark recognition techniques mainly use GPS location information to obtain the candidate images nearby the mobile device, followed by content analysis within the shortlist. This is insufficient since i) GPS often has large errors in dense build-up areas, and ii) direction is underutilized to further improve recognition. In this letter, visual content and two types of mobile context: location and direction, are integrated by the proposed boosting algorithm. Experimental results show that the proposed method outperforms the state-of-the-art methods by about 6%, 11%, and 15% on NTU Landmark-50, PKU Landmark-198, and the large-scale San Francisco landmark dataset, respectively.